The Influence of Financial Knowledge Management and Members' Investment Behavior on the Performance of the Cahaya Cooperative, UPT PLN (Persero) South Sumatra - Inayah Mutiara Beffilia; Isni Andriana; Muizzuddin (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to analyze the role of Financial Knowledge Management (KMK) on Cooperative Performance (KK), with Member Investment Behavior (PIA) as a mediating variable, using a quantitative approach on 80 active members of Cahaya Cooperative UPT Palembang. The results of the instrument validity and reliability tests showed very good consistency (ɑ 0.82). Regression analysis proved that KMK had a significant positive effect on PIA (ꟓ=0.611; R^2=0.520), PIA had a significant positive effect on KK (ꟓ=0.580; R^2=0.490), and KMK also had a significant positive direct effect on KK (ꟓ=0.552). The key finding is that PIA is proven to partially mediate the effect of KMK on KK, which confirms that KMK not only improves performance directly, but also through increasing member investment participation. Theoretically, these results are consistent with Resource-Based Theory (RBT), which positions Financial Knowledge Management as a strategic resource that creates capabilities (member investment behavior) to produce sustainable cooperative performance excellence.